2017
DOI: 10.21315/eimj2017.9.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality among Pre-Clinical Medical Students in Universiti Putra Malaysia and Universiti Malaya, Malaysia

Abstract: Introduction:Poor sleep quality among university students has become an important issue to be concerned as it can hugely influence the students especially on their academic performance. However, there are inadequate studies published on the sleep quality of medical students in Malaysia. Objective: This study aimed at determining the sleep quality of pre-clinical medical students in Universiti Putra Malaysia (UPM) and Universiti Malaya (UM). Methods: This is a cross-sectional study that used self-administered q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…It was depicted that most of the engineering students in this study slept for less than seven hours every night, and this finding is consistent with previous studies by Tien Ngu et al (2017), Ahmed et al (2020), andWondie et al (2021). Also, consistent with this current study's findings, Tien Ngu et al (2017) and Wondie et al (2021) disclosed that the students rated their subjective sleep quality as good despite knowing they were experiencing poor sleep quality.…”
Section: 40 Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…It was depicted that most of the engineering students in this study slept for less than seven hours every night, and this finding is consistent with previous studies by Tien Ngu et al (2017), Ahmed et al (2020), andWondie et al (2021). Also, consistent with this current study's findings, Tien Ngu et al (2017) and Wondie et al (2021) disclosed that the students rated their subjective sleep quality as good despite knowing they were experiencing poor sleep quality.…”
Section: 40 Resultssupporting
confidence: 91%
“…This study's finding is consistent with that of Ahmed et al (2020), which showed that many engineering students reported poor sleep quality. In addition, the percentage of engineering students in this study having poor sleep quality was quite close to that of Al-Khani et al (2019), Nasir and Mohamad (2020), Tien Ngu et al (2017), and Wondie et al (2021 which used medical students as their samples. The comparable findings between these studies show that despite different courses pursued by the students, there are no differences concerning sleep quality levels, which is supported by Ahad (2019).…”
Section: 40 Resultssupporting
confidence: 72%
See 3 more Smart Citations